Dyo-mā: A Female Faith-Healer, and Traditional Medical Practices in Kathmandu - Tandukar, Jyoti (Nepalese Journal of Society and Culture, 2025)
This paper explores the role of Dyo-mā, female faith healers in the Kathmandu Valley, who occupy a significant position in the intersection of spiritual, cultural and traditional medical practices. I have discussed how Dyo-mā contributes to its clientele, who bear different roles sharing and caring as traditional shamans and medicinal practitioners in Kathmandu. I have also explored the spiritual aspects, knowledge, and practices of Dyo-mā or Dyomāyāju. The power of Dyo-mā practices persists despite the influence of modern medical practices in urban settings. The faiths and beliefs of the people are deeply ingrained in their minds and have contributed to their healing as they overcome the psychological and physical challenges they face. The study also situates Dyo-mā alongside other traditional healing systems in Nepal, such as Ayurveda, Amchi (Tibetan-Himalaya medicine), shamanistic practices like dhāmi, Jhānkri and Guruba, which similarly integrate spiritual and herbal healing methods. However, major focus on the role of traditional healing practitioners, specifically Dyo-mā, and her role in healing practice in society.